Pengaruh Literasi Keuangan Syariah, Religiusitas dan Persepsi Mahasiswa Jabodetabek terhadap Keputusan Menggunakan Layanan Perbankan Syariah - Muhammad Ikbal Falevy; Suryani; Prima Dwi Priyatno (An-Nisbah: Jurnal Perbankan Syariah, 2022)
The Islamic banking industry has long been awaited by all Muslim communities who want a banking system based on sharia principles in Indonesia. Even though Islamic banks are now present, there are still many dynamics faced by Islamic banking. This study aims to describe the influence of Islamic financial literacy, religiosity and perceptions of Jabodetabek students on decisions to use Islamic banking services. The research method used in this research is quantitative with data collection method using purposive sampling method with a total sample of 181 respondents who are distributed to students who use Islamic banking in Jabodetabek through questionnaires. The data analysis techniques in this study were validity tests, reliability tests, classical assumption tests, multiple linear regression tests and hypothesis testing with the help of the Statistical Package for the Social Sciences (SPSS) software version 25. The results of this study indicate that the Islamic financial literacy variable, religiosity and perceptions of Jabodetabek students have a positive and significant influence on the decision to use Islamic banking services.